PHYTOCHEMICALS AND ANTIMICROBIAL STUDIES ON COSTUS SPECIOSUS - Dash, Deepti Prangya; Mohanty, Rajashree; Ray, Jassaswi (Journal of Global Pharma Technology, 2024)
The aim of the present study was to investigate antimicrobial activity of methanolic extract of Costus Speciosus (CS). The percentage yield and physical status of the methanolic leaf extract (MECS) and chloroform (CSC) and aqueous fractions Costus Speciosus (CS) are showed. The antibacterial activity of a compound is expressed in terms of its ability to inhibit the growth of bacteria in nutrient broth or agar media. The bacterial growth inhibition can be measured by two methods (Cup plate method and Serial dilution method ) . Nutrient broth has been used for the preparation of inoculum of the bacteria and nutrient agar is used for the evaluation of antibacterial activity. All the Extracted compounds (BMC & BMQ), were found to be effective antibacterial agents. Antifungal activity evaluation against C. Albicans showed that compound BMH also did not possess significant antifungal properties. The study confirms that Costus Speciosus (CS) and all possess antimicrobial activity with different potency against variety of selected microorganisms. The differentiating activities of these extracts encourage developing an ovel broad spectrum antimicrobial herbal formulation in future. Costus Speciosus (CS), Antimicrobial Activity, Antifungal Activity, MECS, BMC & BMQ, BMH, Albicans.